Effect of Ergotamine and its Combination with Vitamin E or Melatonin on Total Antioxidant Status in Migraine Patients - Shahlaa H. Ali; Salim A. Hamadi; Ashwaq N. Al- Jaff (College of Pharmacy University of Baghdad, 2017)
Free radicals and oxidative damage caused by them have being suggested to be involved in the pathogenesis of migraine. These may result from distorted equilibrium of pro-oxidant/anti-oxidant system that continuously generates and detoxifies oxidants during normal aerobic metabolism. Escape of such system from equilibrium leads to damage of cellular elements with the depletion of cellular stores of anti-oxidants material such as glutathione and vitamin E. Therefore, free radical scavengers (vitamin E or melatonin) seems to be of potential benefit as prophylactic anti-migraine therapy by neutralizing free radicals overproduction and possibly preventing formation of highly toxic intermediates (such as nitric oxide). In addition of being powerful antioxidant, melatonin was shown to possess promising effects in modulating severity, frequency and duration of migraine attacks. For this reason the present study was conducted to investigate the involvement of changed anti-oxidant defense (measured as total antioxidant status â€œTASâ€) during migraine attack and the possible modulation of such status by classical anti-migraine therapy (ergotamine), antioxidants (vitamin E and melatonin) and their combination. 23 normal subjects and 21 migraine patients with age range of (17-45) years were enrolled in the study. Patients were diagnosed according to neurologist decision to have migraine with and without aura. Migraine patients were divided into three treatment groups; first group treated with ergotamine alone, second group with ergotamine /vitamin E and third group with ergotamine /melatonin. All groups were advised to take their treatments during attacks. Blood samples were drawn from migraine patients and normal subjects before initiation of therapy and after pain has been relived (from migraine patients only) for the investigation of TAS . The results of the study showed that TAS was significantly lower in migraine patients in comparison to control healthy subjects (P<0.05) with a percent reduction ranged from 35.46% to 43.97%. However, there is no significant difference in the level of TAS among migraine patients (P>0.05). Treatment with ergotamine raised significantly the level of TAS by 157%. The addition of vitamin E or melatonin greatly raised TAS by 179% and 176% respectively. The addition of vitamin E to ergotamine showed superior effect to that when melatonin was added. The greater reduction in TAS seen in this study among migraine patients in comparison to control healthy subjects suggests the presence of generalized decrease in antioxidant defense elements. Elevation of TAS by all treatments was very clear. In conclusion the decrease in TAS can be implicated in the pathophysiology of migraine and enhancement of antioxidant system can add a beneficial effect for the management of migraine headache with the use of antioxidants (vitamin E or melatonin) with classical anti-migraine drug.